Application of Futuristic Concepts in the Design of Film Schools in Medan - Randy Akbar; Cut Nursaniah; Erna Meutia (Jurnal Ilmiah Mahasiswa Arsitektur dan Perencanaan, 2022)
Technological developments from time to time are increasing from time to time, especially in internet-based technology, films are objects that can be entered into the internet so that people no longer need to go out to watch or buy films, because all of that can be obtained via the internet. In this pandemic era, many people spend their time at home, so that many people tend to get bored when they are at home, because of that the need for entertainment which can be on location even at home, one of which is watching movies. For this reason, it is necessary to build a film school where the development of film is increasingly developing from the time and entertainment time during the pandemic in the form of films and graduates from film schools can create their own jobs through the abilities obtained from film schools.